The role of immune response in initiation and progression of chronic kidney disease (Iranian Journal of Kidney Diseases, 2019)
Chronic kidney disease (CKD) is a common disease in the world that has adverse outcomes.  Immune systems and its components have important roles in the initiation, progression and complications of this disease by systemic inflammation.  Regarding the role of kidneys in the body's natural homeostasis and its relationship with other organs, CKD causes impairments in other organs. Patients with chronic renal failure have variety of complications, such as cardiovascular disease, anemia, bone disorders, immune dysfunction and etc., which together culminate in the morbidity and mortality of these patients. Immune dysfunction is one of the most important and serious complications in CKD patients. These patients often suffer from immune suppression and are susceptible to some infections. In this review, we describe some major findings about interactions between the kidney and immune system in CKD.